The Determinants of Smoking Behavior among Teenagers in East Java Province, Indonesia - Martini, Santi (World Bank, Washington, DC, 2013)
The Surabaya youth survey used a modified version of the Global Youth Tobacco Survey questionnaire to investigate knowledge, attitudes and practices concerning smoking among 1,630 students in 40 high schools in Madiun City, Malang City, Jember Regency and Bangkalan Regency in 2003. Factors which predispose, enable, and reinforce smoking were examined to identify where tobacco control interventions might be appropriate and effective. Female students showed an unexpectedly high smoking rate. Students were aware of the health risks associated with smoking but underestimated how addictive cigarettes are. Generally, they found cigarettes affordable and accessible, but those who perceived cigarettes not very easy to obtain smoked less. Schools appeared to be smoker-friendly environments. Students who lived in households with smokers were more likely to smoke, but parental disapproval of smoking was associated with a lower smoking rate. Smokers, in particular, affirm many social and personal reasons to smoke. These findings suggest many possibilities for interventions.